Elements and indicators for identification of quality of primary education - Sučević Vlasta M.; Kerić Mara (Visoka škola strukovnih studija za vaspitače, Kruševac, 2015)
Education is one of the main pillars of the quality of knowledge, and, in turn, social progress in general. There are numerous positions concerning quality of education, some more, and some less detailed. In order to determine the quality of a primary school, for example as 'poor', 'mediocre' or 'excellent', we use, more or less precisely, a certain idea about the value, and thus identify, again with a certain extent of accuracy, the position of the school in question in relation to other schools. In terms of the quality of education, it is necessary to analyze all segments of educational process. This includes the analysis of objectives of educational process, products of quality education as well as adequate and accessible technical-instrumental, that is, operational-procedural level of quality of educational process. Most authors connect the quality of primary education to results, that is, outcomes of education. In order to achieve quality of education, we need to achieve quality of particular components or elements of the whole of education. This paper deals with theoretical review of elements and indicators of quality of basic education, and provides a review of pedagogical strategies and their effect on certain components of quality with the aim to improve the effects on pedagogical and didactical resources of the quality of education.